ENERGI POTENSIAL ROSEN MORSE MENGGUNAKAN PERSAMAAN DIRAC UNTUK KASUS SPIN SIMTERI(K=0)DENGAN MENGGUNAKAN METODE POLYNOMIAL ROMANOVSKI - Alpiana Hidayatulloh; Alpi Zaidah (Lembaga Berugak Baca, 2026)
This research aims to find the energy in the Rosen Morse potential with a kappa value equal to zero and supported by the values ​​of different variables. The method used in this research is the Romanovski polynomial method. o obtain the energy equation for the Rosen-Morse potential, first reduce the Dirac equation to a second-order differential equation of the Hypergeometric type. Through the appropriate variable substitution, an intermediate Hypergeometric equation can be obtained which is then made into a standard differential equation form of the Romanovski polynomial and the energy value cannot be solved analytically, so it is solved with the help of the Matlab application. The energy produced in a state where kappa is equal to zero has energy that increases by providing different n.